Current Research Approaches and Challenges in the Obesogen Field - Chamorro-Garcia, Raquel; Blumberg, Bruce (Frontiers in Endocrinology, 2019)
Obesity is a worldwide pandemic that also contributes to the increased incidence of other diseases such as type 2 diabetes. Increased obesity is generally ascribed to positive energy balance. However, recent findings suggest that exposure to endocrine-disrupting chemicals such as obesogens during critical windows of development, may play an important role in the current obesity trends. Several experimental approaches, from in vitro cell cultures to transgenerational in vivo studies, are used to better understand the mechanisms of action of obesogens, each of which contributes to answer different questions. In this review, we discuss current knowledge in the obesogen field and the existing tools developed in research laboratories using tributyltin as a model obesogen. By understanding the advantages and limitations of each of these tools, we will better focus and design experimental approaches that will help expanding the obesogen field with the objective of finding potential therapeutic targets in human populations.